Monetary valuation of the amenity forest ecological conservation and management attributes in Malaysia - Tom, Chin Kee; Matthew, Nitanan Koshy; Shuib, Ahmad (Inderscience Enterprises, 2022)
Abstract: Incorporating users' preferences, expectations and demands when designing, planning and managing forest reserves for recreational purposes is crucial to success. This is particularly important in countries that have gazetted the forests as recreational forests for the public. This study aims to determine visitors' preferences on ecological and management recreational forest attributes, the levels of attributes and their preferences for particular forest attributes using the choice experiment method. The results indicated that visitors felt the number of workers in the park is sufficient, followed by more information boards (IB) (80% coverage) in the park being needed. Regarding facilities (IF), respondents were looking forward to seeing an improvement in up to 90% of the park's current facilities. In addition, respondents felt that park management should enhance their ecological management efforts in the park. The findings revealed in the AKRF that 83.6% of the respondents were willing to donate on ecological conservation and management. The quantity that participants were willing to donate amounted to RM44/year/family based on the random parameter logit model. The findings may assist policymakers in investigating the relationship between visitors and conservation and management in the AKRF.